Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Évaluation de la validité des preuves présentées dans l’étude intitulée "Language Barriers in Health Care Settings: An Annotated Bibliography of the Research Literature" - Bureau d'appui aux communautés de langue officielle (Santé Canda, 2008)

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Language as a barrier to care for Xhosa-speaking patients at a South African paediatric teaching hospital - Levin, M. E. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Disease is closely linked to the social context in which we live. Difficulty with communication, cultural incompatibility between patients and health care providers and socioeconomic obstacles are important barriers to quality care when doctors and patients come from different backgrounds and speak different languages. Red Cross War Memorial Children's Hospital (RCH) is a paediatric teaching hospital in Cape Town where staff members communicate mainly in English or Afrikaans, while many patients speak Xhosa as their first language. OBJECTIVES: The study aimed to identify barriers to optimal care for Xhosa-speaking parents of patients at RCH. The contribution of language difficulties was assessed as a possible barrier to health care for this group. DESIGN: A questionnaire was developed and administered to 53 Xhosa-speaking parents of children admitted to the short-stay ward at RCH. The questionnaire examined parents' perceptions of barriers to their children's care, using openended questions, closed-ended questions and selection from lists. RESULTS: Parents experienced significant structural and socioeconomic barriers to access of health care for their children. Language and cultural barriers were cited by more parents as a major barrier to health care than structural and socioeconomic barriers. Parents did not have access to same-language practitioners, as only 6% of medical interviews were conducted partly or wholly in the patient's home language. Of the 94% of interviews where no Xhosa was spoken by medical staff, 21% were conducted with the aid of an interpreter (formal or ad hoc) and in 79% no interpreter was used. Parents experienced difficulties with understanding the doctors (64%), making themselves understood (54%) and asking questions (38%). Sixty-nine per cent of parents were dissatisfied with communication between themselves and their doctors and 45% were concerned about negative effects of poor communication on them or their children. Parents tended to blame their own linguistic limitation rather than those of the doctors.
Keywords: Adolescent; Adult; Communication Barriers; Cultural Characteristics; Health Care Surveys; Health Services Accessibility; Hospitals; Pediatric; Hospitals; Teaching; Humans; Language; Middle Aged; Multilingualism; South Africa

Linguistic sensitivity, indigenous peoples and the mental health system in Wales - Madoc‐Jones, Iolo (International Journal of Mental Health Nursing, 2004)
Abstract: This paper presents findings from a pilot research project to explore the significance and availability of mental health services in the medium of Welsh in Wales UK. Based on small‐scale research with Welsh‐speaking mental health service users this article argues that being bilingual can be a significant factor in the complex biopsychosocial matrix that underpins mental health problems amongst Welsh speakers. It also argues that the destructive effects of linguistic oppression and the difficulties of second language communication for mental health service users are such that an appropriate health and social care response in Wales involves providing services in a user's preferred language. Service users’ views about the current state of bilingual service provision in Wales are presented which suggests that insufficient attention is being paid to the linguistic needs of Welsh speakers. Eight principles are proposed for mental health service policy and practice in Wales.

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.
Nombres de pages: 85

Mini Mental State Examinations in English: Are they Suitable for People with Dementia Who are Welsh Speaking? - Morgan, Tracey; Crowder, Ruth (Dementia, 2003)

The effects of a language barrier in a South African district hospital - Schlemmer, A.; Mash, B. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Communication between health workers and patients at Hottentots Holland Hospital (HHH) is hindered by staff and patients not speaking the same language. HHH is a district hospital in the Cape Town Metropolitan District of the Western Cape where staff mainly speak Afrikaans or English and a large number of patients mainly Xhosa. OBJECTIVES: The study aimed to explore the effects of this language barrier on health workers and patients at HHH. DESIGN: Three focus group interviews were held with 21 members of staff and 5 in-depth patient interviews were conducted. RESULTS: The language barrier was found to interfere with working efficiently, create uncertainty about the accuracy of interpretation, be enhanced by a lack of education or training, cause significant ethical dilemmas, negatively influence the attitudes of patients and staff towards each other, decrease the quality of and satisfaction with care, and cause cross-cultural misunderstandings. CONCLUSION: The effects of the language barrier were considerable and persistent despite an official language policy in the province. The training and employment of professional interpreters as well as teaching of basic Xhosa to staff are recommended.
Keywords: Communication Barriers; Health Services Accessibility; Hospitals; District; Humans; Language; Multilingualism; Outcome Assessment; Health Care; Professional-Patient Relations; South Africa; Surveys and Questionnaires

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.